Pharmacological approach on kalanchoe pinnata – a concise report - Shankar, Jai; V, Ajay B; Gowda, Hiteesh; Karthik; R, Bharathi D; M, Rupesh Kumar (International Journal of Indigenous Herbs and Drugs, 2022)
The herbal extract of different parts of the kalanchoe pinnata plant are being used for the treatment of injuries, respiratory infections, diabetes, wound healing, diabetic wound healing, bug stings, and pain and inflammation. This genus has about 125 species. Alkaloids, flavonoids, phenolic compounds, tannins, macro elements, microelements, iron, zinc, vitamins, ascorbic acid, riboflavin, thiamine, and niacin are all present in the plant. It is mainly used in treatment of urinary bladder stones, diarrhea, cold, coughs, fever, headache, pain. It has wide pharmacological properties such as antihypertensive, anti-mutagenic, antibacterial, wound healing, antidiabetic, hepatoprotective, nephroprotective and antioxidant activities.